2017
DOI: 10.18632/oncotarget.22591
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of a novel gene expression profile classifier for the discrimination between metastatic and non-metastatic primary colorectal cancer tumors

Abstract: Despite significant advances have been achieved in the genetic characterization of sporadic colorectal cancer (sCRC), the precise genetic events leading to the development of distant metastasis remain poorly understood. Thus, accurate prediction of metastatic disease in newly-diagnosed sCRC patients remains a challenge. Here, we evaluated the specific genes and molecular pathways associated with the invasive potential of colorectal tumor cells, through the assessment of the gene expression profile (GEP) of cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…A major function of PLPP3 is dephosphorylation of extracellular lysophosphatidic acid, a phospholipid with growth factor-like activity that stimulates tumour cell migration and invasion [52]. PLPP3 displays reduced expression in metastasising (versus non-metastasising) sporadic colorectal cancer [53]. Conversely, SFPR4 , a member of the secreted frizzled-related family that inhibit Wnt signalling by binding to Wnt proteins or to Frizzled receptors, displays decreased expression in M MCTs.…”
Section: Discussionmentioning
confidence: 99%
“…A major function of PLPP3 is dephosphorylation of extracellular lysophosphatidic acid, a phospholipid with growth factor-like activity that stimulates tumour cell migration and invasion [52]. PLPP3 displays reduced expression in metastasising (versus non-metastasising) sporadic colorectal cancer [53]. Conversely, SFPR4 , a member of the secreted frizzled-related family that inhibit Wnt signalling by binding to Wnt proteins or to Frizzled receptors, displays decreased expression in M MCTs.…”
Section: Discussionmentioning
confidence: 99%
“…FN1 is known to interact with FBLN1 in the extracellular matrix and has been implicated in promoting cell migration (Pupa et al, 2002). SRPX2 is a ligand for the urokinase plasminogen activator surface receptor and has been shown to be overexpressed in gastrointestinal cancers and to promote cell migration (Karagiannis et al, 2012;Gutiérrez et al, 2017) . Additionally, expression of classic markers of epithelial cells -CDH1, EPCAM, VIL1, and KRT19 are decreased in patient tumors post-treatment with radio-chemotherapy, and markers of mesenchymal cells are increased ( Figure 4C).…”
Section: Decreased Wnt Signaling In Colorectal Cancer Patients Is Cormentioning
confidence: 99%
“…The appearance of these metastases is usually preceded by the appearance of positive lymph nodes and/or lymphovascular invasion, which are currently the main clinical parameters used to predict the evolution of these tumours [ 4 ]. We [ 5 , 6 , 7 ] and others [ 2 , 8 , 9 ] have recently shown that sCRC metastasis may emerge in the context of a specific genetic tumour background associated or not with other genetic alterations, and that this further affects cellular control of growth and proliferation [ 8 ]. The discovery of those specific genetic alterations that might contribute towards identifying patients with locally aggressive tumours or who are at risk of developing metastases could significantly influence the development of new strategies for the diagnosis and management of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although sCRC is amongst the best characterized solid tumours at the molecular level, the specific genes and molecular mechanisms determining the aggressiveness of the tumour remain to be exhaustively identified. For this reason, we [ 6 , 7 ] and others [ 13 ] have focused on molecular analysis to study the primary tumour and their paired liver metastases in depth. In all these studies, GEP abnormalities have been investigated, as well as altered signalling pathways or miRNAs that regulate the expression of the genes involved in the process of tumour progression.…”
Section: Introductionmentioning
confidence: 99%